Heredity a Revisited Theme in Henrik Ibsen’s ‘A Doll House’ & ‘Ghosts’ - Ismail, Hidaya Ibrahim Hashim; Nur, Hala Salih Mohammed (Journal of English Language and Literature (ISSN: 2368-2132), 2019)
The aim of this paper is mainly focused through the quotation ‘sins of the father are visited upon the son’ the researchers used the critical analytical method to highlight the theme of heredity in Ibsen selected plays. The analysis of the theme showed that the heredity is not only portrayed in the plays but it has traces from his personal life. The fear of becoming like his father very much influences the theme of heredity in the plays. The paper also attempts to link the inheritance theme to the Ibsen’s life. The researchers focused on the Naturalism movement as ground for the reading of the influence it had on the author and its clear significance into the following events of the plays. Light is shed upon the saying ‘sins of the father’s’ for its clear relation to Oswald state.